2011
DOI: 10.1016/j.biomaterials.2011.04.046
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Toll-like receptor pathway in the recognition of orthopedic implant wear-debris particles

Abstract: The inflammatory response to prosthetic implant-derived wear particles is the primary cause of bone loss and aseptic loosening of implants, but the mechanisms by which macrophages recognize and respond to particles remain unknown. Studies of innate immunity demonstrate that Toll-like receptors (TLRs) recognize pathogen-associated molecular patterns (PAMPs) and danger-associated molecular patterns (DAMPS). All TLRs signal through myeloid differentiation factor 88 (MyD88), except TLR3 which signals through TIR d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
112
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 111 publications
(122 citation statements)
references
References 33 publications
7
112
0
1
Order By: Relevance
“…Functional studies have shown that deletion of TLR2 and/or TLR4 in murine systems substantially reduces the in vitro and in vivo responses to titanium [8,37], UHMWPE [40], cobalt-chromium [85], and hydroxyapatite [34] particles. Moreover, similar results have also been obtained for deletion of the myeloid differentiation primary response gene (MyD88) with both PMMA and cobalt-chromium particles [82,85]. MyD88 is an adaptor protein involved in signaling by most TLRs and members of the IL-1 receptor family [51,79].…”
Section: Toll-like Receptorssupporting
confidence: 62%
See 1 more Smart Citation
“…Functional studies have shown that deletion of TLR2 and/or TLR4 in murine systems substantially reduces the in vitro and in vivo responses to titanium [8,37], UHMWPE [40], cobalt-chromium [85], and hydroxyapatite [34] particles. Moreover, similar results have also been obtained for deletion of the myeloid differentiation primary response gene (MyD88) with both PMMA and cobalt-chromium particles [82,85]. MyD88 is an adaptor protein involved in signaling by most TLRs and members of the IL-1 receptor family [51,79].…”
Section: Toll-like Receptorssupporting
confidence: 62%
“…Moreover, there is extensive evidence that endogenous alarmins (also known as danger-associated molecular patterns) can activate TLRs [9,69]. A number of investigators have therefore concluded that TLR activation during aseptic loosening is primarily the result of alarmins rather than PAMPs [13,40,57,75,82]. For example, one of those papers concluded that UHMWPE particles induce production by monocytes of an alarmin known as hsp70 that, in turn, activates TLR4 [40].…”
Section: Toll-like Receptorsmentioning
confidence: 99%
“…TLRs, upon recognition and binding of PAMPS to the receptor surface, initiate an intracellular signaling cascade ultimately resulting in the secretion of a host of inflammatory cytokines attributed to translocation of the NF-κB (nuclear factor kappa-light-chain-enhancer of activated B cells) into the nucleus [65].…”
Section: Toward Gmp Standardmentioning
confidence: 99%
“…These sensory receptors are one of many PRRs responsible for initiation of the innate immune response [ 7 ]. TLRs, upon recognition and binding of PAMPS to the receptor surface, initiate an intracellular signaling cascade ultimately resulting in the secretion of a host of infl ammatory cytokines attributed to translocation of the Nf-kB (nuclear factor kappa-light-chain-enhancer of activated B cells) into the nucleus [ 8 ]. Capsule permeable antigens are secreted by islets, potentially as DAMPs due to hypoxic conditions generated by pericapsular fi brotic overgrowth.…”
Section: Alginate Puritymentioning
confidence: 99%